Experimental evaluation of hybrid propulsion rocket engine operating with paraffin fuel grain and gaseous oxygen - Genivaldo Pimenta dos Santos (2014)
In the last decade the hybrid propulsion has been considering as a viable alternative of chemical energy conversion stored in propellants into kinetic energy. This energy is applied in propulsive systems of manned platforms, maneuvering procedures and even in the repositioning process of micro satellites. It presents attractive features and good balance between performance and environmental impact. Paraffin based grains are the hybrid solid fuels appointed as polymeric fuel substitute. The liquid layer formed on the burning surface ensures high regression rate when driven into the flame front. Paraffin grains allow raw material recovery and reduce the risk of explosion in the presence of erosive burning. The structure of the grain and the control of the liquefying burning surface layer depend on the additives concentration, such as carbon black, which are added to the fuel matrix during the production process. In the solid propellant paraffin based grain a cylindrical center port developed during the centrifugation tends to concentrate carbon black in the outer region of the grain. The influence of carbon black distribution and hardness gradient in paraffin based grain were evaluated in this work. Despite being a well-known material, scarce data on the relation of activation energy (Ea) of paraffin is available. In this work, the kinetic parameters (activation energy and pre-exponential factor) of microcrystalline 140/1450F paraffin have been raised through Thermo Gravimetric Analysis in conjunction with the Arrhenius kinetic mechanism, according to ASTM-E1461. The analysis indicated that the microcrystalline 140/1450F paraffin presents activation energy of 242 kJ.mol-1 and pre-exponential factor from 1.42x1020 min-1 to 2.90x1025 min-1. Ignition was achieved with a 50 W pyrotechnic igniter. Firing tests with 140/1450F paraffin as solid fuel and gaseous oxygen (GOX) as oxidizer were carry on at pressure above 3.8 MPa. The study suggests that multiple thin layers grain may generate burning surfaces with hardness and carbon black concentration almost constant. In this work combustion instability presented by rocket engine was calculated applying the frequency and boundary layer delay time relationship as proposed by Karabeyoglu. The frequency instability up to was evaluated using LabVIEW data acquisition system. In hybrid propulsion the carbon black has been playing a key role in the gas production process on the burning surface, the contribution of carbon black in the combustion instability suppression of hybrid propulsion system with paraffin-based propellant was evaluated. The results confirm the potential use of paraffin base propellant grains loaded with carbon black charge in hybrid propulsion. Paraffin propellants grains doped with carbon black (CB - from 2% to 8%) were burned on the rocket engine test workbench in the Aeronautical Engineering Laboratory / ITA. In the hybrid combustion performance evaluation based on conventional methods approach, it was applied graphical means to visualize the flow path results. Through the flow profile adjustment it was identified a global regression rates values near the practical grain consumption. The model represented graphically the relationships between oxidizer mass flow rate from with injection pressure from and it is recommended as a tool to help the hybrid propulsion performance assessment.